PENGARUH PROMOSI, KENYAMANAN TEMPAT DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN - Arsana, I Wayan Dedy Budha; Ekawati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023DO - 10.24843/EEB.2023.v12.i07.p18, 2023)
The purpose of this study is to explain the effect of promotion, place comfort and brand image on customer loyalty. This research was conducted at Mie Gacoan Renon. The sample used is the consumer of Kedai Mie Gacoan Renon, with purposive sampling method. The data was collected using a questionnaire, the data was analyzed using multiple linear regression analysis techniques. This study also uses validity and reliability tests to determine whether or not the instrument used in this study is feasible. In this study, the analytical techniques used are descriptive statistics, multiple linear regression analysis, classical assumption test, regression coefficient significance test simultaneously (F test) and partial regression coefficient significance test (T test). The results of this study indicate that promotion has a positive and significant effect on customer loyalty of Mie Gacoan Renon. Place comfort has a positive and significant effect on customer loyalty for Mie Gacoan Renon. Brand image has a positive and significant effect on customer loyalty of Mie Gacoan Renon. Promotion, convenience of place and  brand image simultaneously affect customer loyalty of Mie Gacoan Renon